O CEFD/UFSM na atribuição de sentidos à Educação Física Escolar entre 1970 e 2004 - Rosa, Juliano de Melo da (2017)
The present work represents a study about the Physical Education and Sports Centre (CEFD) of Santa Maria Federal University (UFSM) from a historical perspective. The main objective here is to comprehend the different meanings assigned by the CEFD to School Physical Education among the years of 1970 and 2004. This is an initiative that exisists due to the recognition of the significant reach of the institution’s actions in our society and the influence that can represent to the educational initiative mediated by the human moviment at schools. In order to contemplate the intended purpose, the methodology envolved the exectution of interviews about oral hitory, a category of thematic hitories, with five teachers of the graduation course during the mentioned period; the enquiry to document records with information about the Physical Education Centre activities; and the study of bibliographies about the work promoted by the CEFD over the years. The gathered information with the different sources were individually and jointly interpreted, based on the internal logic and the contextual references of the presented contents, taking us to a re-establishment of the educational interventions promoted on the Institution and, with them, to a set of meanings assigned to School Physical Education. The signs points to an excellent formative work developed based on Natural and Exact Sciences, stem from a close link with the sportive phenomenon. This tendency raised implemented learning relations, predominantly, by technical actions, generating, among other things, an instrumental conception of the human motricity on the graduates teaching. This concepts derived to the understanding of what should be Physical Education on the school context, not contemplating, moreover, some legal determinations about the priorities of critical perspectives and the promotions of the undergraduate student autonomy. Diversions of this order were interpreted in the light of the Systemic Thinking and Complex Thinking, considering the notions of systems, leverage points and ecology of the action on the organizational processes institutionally generated. That allowed the recognition of the character of State apparatus and social apparatus presented by the CEFD simultaneously. Which leaded it, among other things, to produce conceptions of School Physical Education based on environmental influences in not necessarily linear logics. Such configurations include as a result of an theoretical-methodological arrangement unrelated with other works, becoming, therefore, original.